Modeling and Simulation of Piecewise Regular Multimode Fiber Links Operating in a Few-Mode Regime. (12th November 2013) - Bourdine, Anton
Abstract : This work presents an alternative model of multimode fiber links with conventional silica weakly-guiding graded-index irregular multimode fibers under a few-mode optical signal propagation generated by laser source. The proposed model is based on the piecewise regular representation. It takes into account launch conditions, differential mode delay, both lower- and higher-order mode chromatic dispersion, differential mode attenuation, and mode mixing and power diffusion occurring due to real fiber irregularity and micro- and macrobends. We present some results of introduced model approbation with following pulse propagation simulations. A close matching with measured pulse responses at the output of test fibers is noticed.